2021
DOI: 10.3390/ijms22094462
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Marrow Microenvironment in the Growth and Development of Malignant Plasma Cells in Multiple Myeloma

Abstract: The development and effectiveness of novel therapies in multiple myeloma have been established in large clinical trials. However, multiple myeloma remains an incurable malignancy despite significant therapeutic advances. Accumulating data have elucidated our understanding of the genetic background of the malignant plasma cells along with the role of the bone marrow microenvironment. Currently, the interaction among myeloma cells and the components of the microenvironment are considered crucial in multiple myel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 185 publications
(220 reference statements)
0
44
0
1
Order By: Relevance
“…Besides, BMSCs have been reported to secrete excessive interleukin-6 (IL-6) to promote and support the growth of MM cells ( Arnulf et al, 2007 ). In addition, another study has revealed that BMSCs could protect MM cells from destruction by reactive cytotoxic T cells (CTL) and NK cells, triggering immune escape ( Giannakoulas et al, 2021 ). In turn, MM cells could also educate and manipulate BMSCs to make a more conducive microenvironment for MM cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, BMSCs have been reported to secrete excessive interleukin-6 (IL-6) to promote and support the growth of MM cells ( Arnulf et al, 2007 ). In addition, another study has revealed that BMSCs could protect MM cells from destruction by reactive cytotoxic T cells (CTL) and NK cells, triggering immune escape ( Giannakoulas et al, 2021 ). In turn, MM cells could also educate and manipulate BMSCs to make a more conducive microenvironment for MM cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a heterogenous metabolic pattern in baseline positron emission tomography/computed tomography (PET/CT) has been recently associated with adverse prognosis in patients with MM [ 20 ]. Therefore, response to antimyeloma treatment might be indirectly correlated to impaired metabolic status and changes in microenvironment [ 21 , 22 ]. Furthermore, metabolic signatures may have a prognostic value in patients with MM.…”
Section: Introductionmentioning
confidence: 99%
“…The BM microenvironment has a key supportive role for myeloma growth and progression, with distinct underlying biology at different disease stages [13,15,36,37]. Various BM subsets interact constantly and dynamically with myeloma cells and contribute to the complex immunomodulatory functions induced, as well as drug refractoriness [38,39].…”
Section: Discussionmentioning
confidence: 99%